2003
DOI: 10.1080/1042819031000119208
|View full text |Cite
|
Sign up to set email alerts
|

Improved Therapeutic Outcome Following Combination Immunogene Vaccination Therapy in Murine Myeloma

Abstract: Increasing evidence suggests a role for immunologic vaccination and therapy in the management of minimal residual myeloma. We have previously demonstrated a synergistic effect of combining the Th1 stimulating cytokine IL-12 with the co-stimulatory molecule CD80 in murine myeloma vaccination therapy. We reasoned that the efficacy of such treatment might be further improved by incorporating additional gene products which enhance the function of antigen presenting cells. Studies were therefore conducted with muri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
2
1
Order By: Relevance
“…Our study showed that the highest SIR of cancer in chronic dialysis patients was that for bladder cancer (SIR: 8.2, 95% CI: 6.7-9.9) compared to that in their healthy counterparts. This is different from the international collaborative studies [6,14,24] which found that kidney cancer had the highest SIR of cancers in chronic dialysis patients. The reason for this discrepancy is unknown, but it may be associated with the heavy consumption of some Chinese herbal products or compound analgesics in the Taiwanese population [22,25].…”
Section: Discussioncontrasting
confidence: 93%
“…Our study showed that the highest SIR of cancer in chronic dialysis patients was that for bladder cancer (SIR: 8.2, 95% CI: 6.7-9.9) compared to that in their healthy counterparts. This is different from the international collaborative studies [6,14,24] which found that kidney cancer had the highest SIR of cancers in chronic dialysis patients. The reason for this discrepancy is unknown, but it may be associated with the heavy consumption of some Chinese herbal products or compound analgesics in the Taiwanese population [22,25].…”
Section: Discussioncontrasting
confidence: 93%
“…Li et al [78] investigated vaccines consisting of a retroviral-transduced myeloma cell line (B9BM1) expressing single or combinations of transgenes (GM-CSF, IL-12, CD80, Flt3L) in a mouse model. They demonstrated that the combined use of GM-CSF, IL-12, CD80 is superior to the use of any single gene product in the protection against subcutaneous challenge with parental tumor cells.…”
Section: Gene Therapy For Multiple Myelomamentioning
confidence: 99%
“…Li et al (1999) investigated vaccines consisting of a retroviral transduced myeloma cell line (B9BM1) expressing single or combinations of transgenes (GM‐CSF, IL‐12, CD80, Flt3L) in a mouse model. They demonstrated that the combined use of GM‐CSF, IL‐12 and CD80 is superior to the use of any single gene product in the protection of s.c. challenge with parental tumour cells.…”
Section: Immunomodulatory Gene Therapy For Multiple Myelomamentioning
confidence: 99%